Phenotypic Detection of Extended Spectrum Beta-Lactamase Production in Clinical and Non-Clinical Isolates of Klebsiella species of Animal Origins in Abeokuta, Nigeria (2022)
Production of extended-spectrum (3-lactamases (ESBLs) confer resistance to P-lactam antibiotics. This study investigated thè presence of ESBL-producing Klebsiella spp in clinical and non-clinical samples froni different animai species in Abeokuta, Nigeria. The species of Klebsiella were determined by biochemical characterization (Oxoid Microbact GNB 24E®), while phenotypic ESBL-production was confirmed by using thè cefpodoxime and cefpodoxime/clavulanic acid combination disc kit. Ninety-five Klebsiella isolates were investigated in this study. Fifty-five (57.9%) of thè isolates were obtained ffom thè faeces of apparently healthy animals while 40 (42.1%) were fram clinical samples. The Klebsiella isolates were identified as follows: K. oxytoca (34.7%), K. pneumoniae (26.3%), K. ozaenae (18.9%), K. terrigena (13.7%), K. rhinooscleromatis (5.3%), K planticola (1.1%). Eight (8.4%) out ofthe 95 isolates of Klebsiella spp were identified as ESBL-producers. These included four isolates of Klebsiella pneumoniae, three of Klebsiella oxytoca and one of Klebsiella ozaenae. Five out of thè eight ESBL-producing isolates were ffom clinical samples while three isolates were ffom thè faeces of apparently healthy animals. The ESBL- producing isolates were 100% resistant to ampicillin, cefotaxime, ceftazidime, cefpodoxime, streptpmycin, tetracycline, compound sulfonamide, trimethoprim/sulphomethoxazole, and nalidixic acid. Apparently healthy carriers and sick animals can serve as sources of transmission of ESBL-producing Klebsiella spp to other animals and humans.